Investigation of non-charging exposure conditions for insulating resist films in electron beam lithography. (15th April 2021) - Kubo, Kento; Kojima, Kentaro; Kono, Yoshinobu; Kotera, Masatoshi
Abstract: When the electron beam (EB) irradiates insulating films on a conducting substrate, the film charges positively or negatively, depending on the condition. The surface potential distribution is measured using an electrostatic force microscope installed in the specimen chamber of a scanning electron microscope. The multiple backscattering phenomenon of electrons between the specimen and the bottom of the objective lens electrode causes a global charging even a few millimeters away from the EB irradiation area. This charging can be suppressed by applying −5 V to the specimen. On the other hand, the charge in the irradiation area changes depending on the exposure dose. When the dose is small, it is positively charged, but when the exposure dose is large, it is negatively charged. However, as the dose increases, it becomes positive again. When the insulating film is irradiated with an EB, the charging potential disappears twice depending on the irradiation dose, and the electric potential distribution was found to be M-shaped and W-shaped. We propose a model to explain this phenomenon.